A mechanism for Thawing the credit markets - Edi Karni (The Johns Hopkins University, Department of Economics, 2009)
This paper describes a mechanism designed to induce commercial banks to increase their willingness to extend loans in an economic environment characterized by increased uncertainty and diminished expectations. This mechanism is a new tool for the conduct of monetary policy to combat recessions.
Keywords: G01; G10; D82; D86; 330; Mechanism design; credit markets; incentive scheme; Mechanism Design; Asymmetrische Information; Kreditmarkt; Vertragstheorie